Impact of Various Modification Methods on Physicochemical and Functional Properties of Starch: A Review. (14th November 2022) - Sinhmar, Archana; Pathera, Ashok Kumar; Sharma, Somesh; Nehra, Manju; Thory, Rahul; Nain, Vikash
Abstract: Starch is extensively used in food applications for process convenience and to improve the quality of food products at industrial levels. The contemporary research on starch has created lots of scientific information that provides a base for interventions in food formulations using starch as an active ingredient. The native starch has some limitations, i.e., low swelling and solubility, low thermal resistance, low shear rates, etc. Modification of starch results in altered properties of starch. To modify starch, various modification methods such as physical, chemical, enzymatic, and genetic methods are used which enhances the starch applications at the commercial level. In the physical modification of starch, the chemical structure of starch is not affected while in the case of chemical modification there is an introduction of a functional group in starch granules. The modified starches are used in various industries such as food, pharmaceutical, paper, and textile industries. The purpose of this manuscript is to provide a detailed overview of the physicochemical, morphological, and rheological properties of native and modified starch. Abstract : This review covers the effect of physical and chemical modifications on the various properties of starch. The functional, physicochemical, rheological, pasting, and film‐forming properties of starch are improved by various modification methods, leading to increased starch application at the commercial level.